(3GdfLe GdhgGL aj TQM GdefgGLs - (3eMeO Hf ehSi Hf YjSi GdOejQj GdTGaYj , ceGd GdOjf CHh GdHbGA,J (B808 (3g` s
(3ChdgG (B:s
(3cJGH GdLQGM gh HcSQ GdLje LeY LQGMI s
(3BNQgG (B:s
(3hfNJe GdcJGH HeG (B[(3HOCfG(B] (3Hg ef MeO Gddg GdPi jHOF hjYjO fLR GdLRA GdQGHY s
(3GdcJGH GdeTQhM(B: (3efgGL GdWGdHjf ddfhhis
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3QGLY HbjI GdCLRGA (B-(3heYdheGJ GdfSN(B- (3aj GdfSN(B: 79 (3chjJ h (B80 (3chjJ HLRFjgeG s
(3ai BNQ GdhQbI eG jOd Ydi GdfSNI fSNJ ef fSNI efbhdI Yf fSNI GdeDda s
(3bQf GdfSN (B:s
Keywords: (3Gdabg GdTGaYjs